Macrognathus aral (Bloch and Schneider 1801): Growth, condition, age, mortality, recruitment and exploitation in running and stagnant ecosystems in Gandak Basin, India: Life history of M. aral under running and stagnant ecosystems - Kumar, Ravi; A. K. Jaiswar,; Laxmi Prasad,; Sarma, Kamal; Asha T. Landge,; B.B. Nayak,; Ahirwal, S. K.; K.G. Mandal, (Indian Journal of Fisheries, 2024)
Growth and fishery of Macrognathus aral were studied from an oxbow lake Matwali-Majhariyamaun and the river Dhanauti in Gandak Basin, India based on 367 and 451 specimenscollected from the oxbow lake and the river, respectively through weekly sampling fromJune 2020 to May 2021 . The length-weight relationship revealed negative allometric growth(b